Pengaruh Tingkat Pendidikan, Penggunaan Teknologi Informasi dan Pengendalian Internal Terhadap Kualitas Laporan Keuangan: (Studi Empiris pada BUMDES di Kecamatan Dawan) - Werdhiyanti, Ni Putu Putri Ayu; Indraswarawati, Sang Ayu Putu Arie; W, Rai Dwi Andayani (Hita Akuntansi dan Keuangan, 2025)
The quality of financial reports is influenced by several factors, namely Education Level, Use of Information Technology, and Internal Control. This study aims to examine the impact of education level, use of information technology, and internal control on the quality of financial reports, focusing on BUMDES in Dawan District. Multiple linear regression analysis was conducted using the SPSS program, incorporating descriptive statistical tests, F test, t test, data quality assessment, classical assumption testing, hypothesis testing, and coefficient of determination testing (Adjusted R2). The population comprised all BUMDES entities, totaling 107 from 8 BUMDES. Purposive sampling was employed, resulting in a total sample size of 43 respondents. The findings indicate that education level, use of information technology, and internal control significantly and positively influence the quality of financial reports. The study suggests that BUMDES should invest in improving and enhancing human resources through education and technology utilization to ensure the production of high-quality financial reports. Quality financial reports facilitate decision-making processes and the achievement of organizational goals for BUMDES.